Effects of fertilization, burning, and grazing on plant community in the long-term fenced grasslands - Guanghua JING; Wei LI; Kailiang YU; Zak RATAJCZAK; Robert L. KALLENBACH; Jimin CHENG (Plant, Soil and Environment, 2017)
Fencing is the common management practice to restore degraded grasslands. However, long-term fencing decreases grassland productivity and species diversity. The study was therefore conducted as a three-year (2011-2013) experiment with a randomized complete block in a grassland fenced for 20 years in the Loess Plateau of China, and the effects of fertilization, burning and grazing on aboveground biomass, species and functional group composition, species and some functional group diversity were analysed. Our results showed that the functional group of perennial bunchgrasses dominated the grassland regardless of management practices. However, burning altered species composition (i.e. the unpalatable species, Artemisia sacrorum) more significantly than fertilization or grazing, and surprisingly, nearly quadrupled the functional group of shrubs and semi-shrubs. Fertilization had a positive effect on the aboveground biomass (44.0%), while clearly reducing species diversity (21.9%). Grazing decreased aboveground biomass, but increased species diversity by 15.9%. This study indicated that fertilization influenced plant community through its impact on aboveground biomass, while burning changed plant community by altering dominant species. Thus, it was concluded that fertilizer could further improve community biomass while burning reduced the edibility of grass. Grazing could be carried out to enhance the biodiversity in the long-term fenced grasslands.